Dilemma’s regarding vertebral fractures in children with acute lymphoblastic leukemia (ALL) - Pluijm, Saskia.M.F.; te Winkel, Mariel L.; van den Heuvel-Eibrink, Marry M. (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2012)
Acute lymphoblastic leukemia (ALL) is the most frequently occurring type of cancer in children, which currently, due to optimized stratification and treatment regimens, has been become curable in 80-90% of all cases (1). The increasing number of long term survivors has resulted in gain of knowledge and increased awareness of complications that may already occur during treatment as well as later in life.